Faculty Education of Sports Journalists in Montenegro and Serbia - Miomir Maros; Tamara Djukic (Journal of Anthropology of Sport and Physical Education)
In this paper we will examine the study of sports journalism in our country and in the world. In the United States there is sports journalism as a special study program at faculties of journalism, it lasts for four years and it is represented at well-known universities. It takes two years to acquire a master’s degree. Their studies include subjects about sports discipline, besides multimedia subjects, and obligatory professional practice. In England, the biggest diff erence is that obtaining a bachelor’s degree requires three years of schooling. In the region, there is a study programs of sports journalism at the Faculty of Sports and Physical Education in Niksic since 2007, as well as at a private University Union in Belgrade. Many leading journalists in sports and informative journalism studied at the Faculty in Niksic. Regarding to the region, while we were analyzing the study program in Niksic, we noticed a greater number of subjects in sports science than in journalism. The number of sports subjects is almost symbolically smaller at the Belgrade University. Unlike before, the Montenegrin study program is now academic and free for students enrolled regularly, who study together with sports trainers for the fi rst two years, and in the third year they choose a sports journalist module.